Nanoelectronics : quantum engineering of low-dimensional nanoensembles - Arora, Vijay Kumar (CRC Press, Taylor & Francis Group, 2015)
Brings the Band Structure of Carbon-Based Devices into the Limelight A shift to carbon is positioning biology as a process of synthesis in mainstream engineering. Silicon is quickly being replaced with carbon-based electronics, devices are being reduced down to nanometer scale, and further potential applications are being considered. While traditionally, engineers are trained by way of physics, chemistry, and mathematics, Nanoelectronics: Quantum Engineering of Low-Dimensional Nanoensembles establishes biology as an essential basic science for engineers to explore. Unifies Science and Engineering: from Quantum Physics to Nanoengineering Drawing heavily on published papers by the author, this research-driven text offers a complete review of nanoelectronic transport starting from quantum waves, to ohmic and ballistic conduction, and saturation-limited extreme nonequilibrium conditions. In addition, it highlights a new paradigm using non-equilibrium Arora's Distribution Function (NEADF) and establishes this function as the starting point (from band theory to equilibrium to extreme nonequilibrium carrier statistics). The author focuses on nano-electronic device design and development, including carbon-based devices, and provides you with a vantage point for the global outlook on the future of nanoelectronics devices and ULSI. Encompassing ten chapters, this illuminating text: Converts the electric-field response of drift velocity into current-voltage relationships that are driven by the presence of critical voltage and saturation current arising from the unidirectional drift of carriers Applies the effect of these scaled-down dimensions to nano-MOSFET (metal-oxide-semiconductor field-effect transistor) Considers specialized applications that can be tried through a number of suggested projects that are all feasible with MATLAB® codes Nanoelectronics.